Structural Studies of the 3′,3′-cGAMP Riboswitch Induced by Cognate and Noncognate Ligands Using Molecular Dynamics Simulation - Chaoqun Li (International Journal of Molecular Sciences, 2018)
Riboswtich RNAs can control gene expression through the structural change induced by the corresponding small-molecule ligands. Molecular dynamics simulations and free energy calculations on the aptamer domain of the 3′,3′-cGAMP riboswitch in the ligand-free, cognate-bound and noncognate-bound states were performed to investigate the structural features of the 3′,3′-cGAMP riboswitch induced by the 3′,3′-cGAMP ligand and the specificity of ligand recognition. The results revealed that the aptamer of the 3′,3′-cGAMP riboswitch in the ligand-free state has a smaller binding pocket and a relatively compact structure versus that in the 3′,3′-cGAMP-bound state. The binding of the 3′,3′-cGAMP molecule to the 3′,3′-cGAMP riboswitch induces the rotation of P1 helix through the allosteric communication from the binding sites pocket containing the J1/2, J1/3 and J2/3 junction to the P1 helix. Simultaneously, these simulations also revealed that the preferential binding of the 3′,3′-cGAMP riboswitch to its cognate ligand, 3′,3′-cGAMP, over its noncognate ligand, c-di-GMP and c-di-AMP. The J1/2 junction in the 3′,3′-cGAMP riboswitch contributing to the specificity of ligand recognition have also been found.